Structural Change, Aggregate Growth And Government Services - Denis Stijepic; Helmut Wagner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Recent literature studies structural change and aggregate dynamics in neoclassical multi-sector growth models. A central aspect of this literature is the explanation of Kaldor-Kuznets-stylized-facts , which state that massive structural change takes place while aggregate-dynamics are relatively stable in the long-run. We present a growth model analysing the role of government in structural change and aggregate growth. We show that, besides distortionary effects on the sector structure, the provision of government services has an impact on the intertemporal elasticity of substitution of the representative household and, thus, on aggregate dynamics. These results can be used to explain the Kaldor-Kuznets-facts.
Keywords: O41; O38; O14; 330